2015
DOI: 10.33549/physiolres.932950
|View full text |Cite
|
Sign up to set email alerts
|

Slow Breathing Training Reduces Resting Blood Pressure and the Pressure Responses to Exercise

Abstract: Slow breathing training reduces resting blood pressure, probably by modifying central autonomic control, but evidence for this is lacking. The pressor response to static handgrip exercise is a measure of autonomic control and the aim of this study was to determine whether slow breathing training modulates the pressor responses to exercise of untrained muscles. Twenty hypertensive patients trained for 8 weeks, 10 with unloaded slow breathing (Unloaded) and 10 breathing against an inspiratory load of 20 cm H2O (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
31
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 33 publications
2
31
0
Order By: Relevance
“…Patients with essential hypertension show exaggerated responses to muscle contraction, and BP remains high after the end of exercise if the blood supply is occluded, indicating an increased sensitivity of the metaboreflex (Delaney et al, 2010;Greaney et al, 2014;Sausen, Delaney, Stillabower, & Farquhar, 2009), and this can be reversed by SLB training (Jones et al, 2015). But how SLB affects these processes is not clear.…”
Section: Physiological Changes In Hypertension and Slbmentioning
confidence: 99%
“…Patients with essential hypertension show exaggerated responses to muscle contraction, and BP remains high after the end of exercise if the blood supply is occluded, indicating an increased sensitivity of the metaboreflex (Delaney et al, 2010;Greaney et al, 2014;Sausen, Delaney, Stillabower, & Farquhar, 2009), and this can be reversed by SLB training (Jones et al, 2015). But how SLB affects these processes is not clear.…”
Section: Physiological Changes In Hypertension and Slbmentioning
confidence: 99%
“…The research on the effect of respiration on HRV has become a hot topic in recent years [10,11].Previous studies have demonstrated that respiration is one of important influencing factors for HRV [12,13]. Cicek S et al [14] confirmed that deep and slow breathing can make people turn from depression to relaxation, and improve the regulation function of human organs or autonomic nerves, so as to improve the adaptability of human body.…”
Section: Introductionmentioning
confidence: 99%
“…The research on the effect of respiration on HRV has become a hot topic in recent years [9][10].Previous studies have demonstrated that respiration is one of important influencing factors for HRV [11,12]. Cicek S et al [13] confirmed that deep and slow breathing can make people turn from depression to relaxation, and improve the regulation function of human organs or autonomic nerves, so as to improve the adaptability of human body.…”
Section: Introductionmentioning
confidence: 99%
“…One-to-one telephone follow-up or home visit: The patient will be followed up after Practice time: The total time per day is more than 30min [25], which can be delivered in batches, but at least 10 minutes at a time and at least 5 times a week [12].…”
mentioning
confidence: 99%